APLIKASI E-LEARNING BERBASIS WEB SEBAGAI MEDIA PEMBELAJARAN PADA JURUSAN IPA DI SMA NEGERI 1 PANYIPATAN, KABUPATEN TANAH LAUT - Rahimah, Rahimah; Sholeha, Eka Wahyu (P3M Politeknik Negeri Tanah Laut, 2023)
Learning media plays an important role in a learning system. However, the COVID-19 pandemic several years ago changed many things in the learning system. Therefore, various applications are needed that are able to support distance learning when unforeseen things happen, such as natural disasters or disease outbreaks. Therefore, various applications were created so that learning can be done at any time. The purpose of building this application is to facilitate students and teachers in carrying out the teaching and learning process, especially science major students as users, where the learning process is an activity carried out by a teacher who serves as a presenter and students as recipients. This research uses a descriptive qualitative approach method. The conventional teaching and learning process is not in accordance with the government program which recommends an online teaching and learning process. SMAN 1 Panyipatan is one of the high schools that still uses conventional methods, it’s still less efficient because the media used does not attract student interest. Apart from that, students are also given assignments manually, such as giving paper assignments, reading questions directly or writing questions on the blackboard. The solution to this problem can be solved by building a web-based e–Learning media application in the science department at SMAN 1 Panyipatan. This application was built using the PHP programming language and data storage uses a MySql database which is expected to help students and teachers in carrying out the teaching and learning process. Diagram design uses Entity Relationship Diagram (ERD). Key Words: Application, E–Learning, Learning Media, Web.